Classroom action research: increasing learning interest of Grade IV students through the TGT model assisted by Quizwhizzer - Elita Hermawanti; Grasianus Agresspa Aga Prasetya; Nensi Desiana Purnamasari; Ratnasari Dyah Utami; Nur Laili Maulidah (Journal Focus Action of Research Mathematic (Factor M), 2025)
Amid growing interest in integrating digital tools to enhance student engagement, this study aims to enhance fourth-grade elementary students' interest in learning mathematics by implementing Quizwhizzer as a learning medium. The research employs a Classroom Action Research (CAR) design, consisting of two cycles, each comprising two sessions. Each cycle follows the stages of planning, action implementation, and reflection. In the first cycle, questionnaire results indicated that 62.07% of students had low learning interest. However, 96.55% of students demonstrated high interest in the second cycle. These findings suggest a significant increase in students’ interest in learning mathematics following using Quizwhizzer. The study concludes that Quizwhizzer is an effective tool for fostering learning interest. Nonetheless, challenges related to time and classroom management were encountered, prompting a recommendation for better planning and management in future implementations.